Price fixing in the memory market [DRAM prices]. - Moore, S.K (IEEE spectrum)
This work focuses on the investigations conducted by the US Department of Justice on the allegations of price fixing in the memory industry. It discusses the details of the case against Infineon Technologies AG, which plead guilty to participating in an international conspiracy to fix prices for dynamic random access memories (DRAM) sold to certain PC and server makers in the US. Regardless of how much of an impact the conspiracy had on price, the fact that Infineon agreed to plead guilty indicates that others were involved, and there will be more fines, as well as penalties and perhaps even jail sentences to come.